Pengembangan Bahan Ajar Menulis Cerpen Berbasis Pengalaman Siswa Kelas XI SMK - Veronika Hanyaq Himang; Widyatmike Gede Mulawarman; M. Ilyas (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2019)
This research has some purposes: (1) describing the design for development of teaching materials for writing short story based on students’ experience, (2) describing the learning implementation of writing short story based on students’ experience, and (3) measuring the quality of teaching materials for writing short story based on students’ experience which is marked from validity, practicality, and effectivity. This research uses research and development method adapted from ten development methods by Borg & Gall consist of necessary analysis, plan, product initial draft organization, product design validity test, product design revision, trial I, product revision II, trial II, final product revision, and dissemination and implementation. The developed teaching materials quality could be seen from the validity test result which shows 90% as the material score, 88% as language score, 89% as presentation score, and 90% as graphics score which result 90% as the average value that means very valid criteria. The result of practicality test could be seen from the score of RPP (lesson plan) implementation which shows 92%, teachers’ response score which shows 89%, and students’ response score which shows 87% that result 89% as the average value which means very practical criteria. The result of effectivity test could be seen from teachers’ activity score which shows 93%, students’ activity score which shows 92%, and the result of students’ short story writing which shows 81% that result 89% as the average that means very effective criteria. Therefore, the researcher concludes the result for development of teaching materials for writing short story based on vocational high school (SMK) students’ experience is stated very valid, very practical, and very effective for used as teaching materials for writing short story based on vocational high school (SMK) grade XI students’ experience.